Jazz na Slovensku v období fašizmu - Yvetta Kajanová (Musicologica Brunensia, 2019)
This study presents new findings about jazz music in Slovakia at the time of World War II. Research has discovered that during the fascist Slovak State semi-professional orchestras consisting mainly of Romani and Jewish musicians also played jazz in small towns, where they were less conspicuous to the Nazis. Jazz ensembles and Romani bands substituted for the shortage of orchestras needed for live broadcasts. One special category was "military jazz". Divisions of Hlinka Youth also included jazz bands and, paradoxically, these were considered as part of youth education. The theatres in Zvolen, Nitra, and Prešov had jazz orchestras performing in their shows. The press of the time featured ensembles, such as the Hans Knauer Orchestra, the Perschitz Orchestra, and the František Prášil Orchestra, whose names have not been mentioned until now by any other theorists. Newspapers offered a rather "glorifying" and "optimistic" interpretation of jazz, which significantly contrasted with the offensive and racist attacks on the Czech "potápka" [duck/grebe] jazz subculture.